Determination of Cost of Goods Produced in Processed Agribusiness Based on Mangosteen Peel Flour - Linar Humaira; Asmanur Jannah; Anna Fitriani (Universitas Djuanda, 2022)
The Peasant Women's Group is a forum that provides opportunities for women to advance in the agricultural sector, one of which is the Pelangi Gunung Suling, located in Barengkok Village, Leuwiliang District, Bogor Regency. This group focuses on agribusiness-processed agricultural products. But in determining the cost of goods produced by processed products, they are still based on estimates only; for this reason, it needs to be studied in determining the cost of goods produced in processed agribusinesses based on Mangosteen peel flour. This study aims to determine the cost of goods produced to determine the selling price of processed cookies produced from mangosteen peel flour. The research method is used purposively or intentionally in the Gunung Suling farmer women's group through recording during the production and documentation process and analyzed by descriptive analysis with a quantitative approach and calculation analysis using the full costing method. The results showed that the calculation of the cost of goods produced by mangosteen peel pao cakes charges raw materials of IDR 89,771 per production per day. In contrast, direct labor costs of IDR 50,000 with overhead costs only consider baking paper, fuel gas, and packaging only Rp. 21,800, -. The total production cost to produce 80 pao cakes per day is IDR 151,671, so the cost of goods produced per piece is IDR 2,020. Using the full costing method, a reasonable selling price of IDR 2,121.86 is obtained; this method can cover all production costs of making pao cakes per piece per production. Determining the cost of goods can be used as a basis for determining the selling price of the production of pao cakes made from additional mangosteen skin flour